2016
DOI: 10.21037/atm.2016.08.58
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive agents for the treatment of sepsis

Abstract: The article describes some commonly used vasoactive agents in patients with septic shock. Depending on their distinct pharmacological properties, their effects on vascular bed and cardiac function are different. For example, dopamine has equivalent effect on heart and vasculature, which can result in increases in cardiac output, mean arterial pressure and heart rate. Dobutamine is considered as inodilator because it has potent effect on cardiac systole and vasculature. Patients with sepsis and septic shock som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 76 publications
0
13
0
1
Order By: Relevance
“…Daher liegt es nahe, einen therapeutischen Ansatz in der Herzfrequenzreduktion bei Patienten mit septischer Kardiomyopathie zu sehen [115]. Der Einsatz von Esmolol zur Kontrolle der Herzfrequenz in der Sepsis wurde als offene, randomisierte Phase-2-Studie in einem Zentrum an insgesamt 144 Patienten im septischen Schock überprüft [74].…”
Section: β-Rezeptoren-blockerunclassified
“…Daher liegt es nahe, einen therapeutischen Ansatz in der Herzfrequenzreduktion bei Patienten mit septischer Kardiomyopathie zu sehen [115]. Der Einsatz von Esmolol zur Kontrolle der Herzfrequenz in der Sepsis wurde als offene, randomisierte Phase-2-Studie in einem Zentrum an insgesamt 144 Patienten im septischen Schock überprüft [74].…”
Section: β-Rezeptoren-blockerunclassified
“…Sepsis is one of major pathological features in ICU patients, and can cause failure of multiple organs and even death (Antonucci et al, 2014;Polat et al, 2017;Dellinger, 2013). The heart is one of the sensitive organs in sepsis (Rudiger and Singer, 2013;Zhang and Chen, 2016), which is characterized by ventricular dilation, reduced ventricular ejection fraction, and abnormal cardiac diastolic and contractility (Fernandes and de Assuncao, 2012;Niederbichler et al, 2006;Vieillard-Baron et al, 2008). Furthermore, heart disease is the main cause of a high mortality rate in sepsis (Court et al, 2002;Parrillo, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the primary outcome of this study was negative, as well as the most secondary endpoints. Besides, the large randomized controlled trial [ 22 ] indicated that levosimendan was associated with a higher risk of supraventricular tachyarrhythmia compared to control and another severe side effect of levosimendan, such as severe vasoplegia that might be difficult to control, should be in attention [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis indicated that levosimendan was associated with significantly reduced risk of death as compared to the conventional inotropes [ 20 ]. A recent review article also illustrated that Levosimendan might be potentially beneficial in reducing mortality risk [ 21 ]. However, one recently large trial demonstrated controversial result.…”
Section: Introductionmentioning
confidence: 99%